1993
DOI: 10.1161/01.hyp.21.5.624
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of arterial myosin in experimental renal hypertension in the dog.

Abstract: We compared myosin samples isolated from iliac-femoral arteries of control and renal (stenosis) hypertensive dogs to determine the effects of increased blood pressure on the characteristics of the myosin. The ratio of 204-kd (SM-1) to 200 -kd (SM-2) myosin heavy chains was approximately 1:0.75 for myosin from the iliac-femoral artery of normotensive dogs. This was not altered significantly in response to hypertension. Both SM-1 and SM-2 myosin heavy chains cross-reacted with antibody against smooth muscle myos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…Quantitation of heavy chain isoforms and Western blot analysis. The SM1 and SM2 myosin heavy chains were separated by slow electrophoresis of denatured protein on highly porous SDS-polyacrylamide gels (4.5%) as previously described (36). After having been stained with Coomassie blue, proteins were quantitated by scanning densitometry with a Bio-Rad GS-700 imaging densitometer.…”
Section: Methodsmentioning
confidence: 99%
“…Quantitation of heavy chain isoforms and Western blot analysis. The SM1 and SM2 myosin heavy chains were separated by slow electrophoresis of denatured protein on highly porous SDS-polyacrylamide gels (4.5%) as previously described (36). After having been stained with Coomassie blue, proteins were quantitated by scanning densitometry with a Bio-Rad GS-700 imaging densitometer.…”
Section: Methodsmentioning
confidence: 99%
“…The extracted muscle proteins present in the supernatant were separated from cell membrane and connective tissue fractions by centrifugation (13,000 g for 20 min). The MHCs SM1 and SM2 were separated by electrophoresis of the supernatant on large (16 ϫ 16 cm) 4.5% SDS-polyacrylamide slab gels (1 mm thick) as previously described (60). Coomassie brilliant blue-stained proteins were quantified by scanning densitometry of the gel using the Bio-Rad GS-700 imaging densitometer and Bio-Rad Quantity One program described above.…”
Section: Gel Electrophoresis and Western Blot Analysismentioning
confidence: 99%
“…Studies on uterine smooth muscle indicate that the composition of the myosin isoforms is altered during hypertrophy [34]. We have demonstrated that the arterial myosin from normotensive and hypertensive dogs shows no difference in the composition of the SM1 and SM2 isoforms [53]. However, analysis of the peptides from myosin heavy chains by finger printing reveals quantitative and qualitative differences in arterial myosin from normotensive and hypertensive dogs [53].…”
Section: Figmentioning
confidence: 80%
“…We have demonstrated that the arterial myosin from normotensive and hypertensive dogs shows no difference in the composition of the SM1 and SM2 isoforms [53]. However, analysis of the peptides from myosin heavy chains by finger printing reveals quantitative and qualitative differences in arterial myosin from normotensive and hypertensive dogs [53]. The actin-activated ATPase activity of myosin isolated from arteries of hypertensive dogs is two-fold that of normals ( Table 1).…”
Section: Figmentioning
confidence: 81%